Atlantic salmon water pathogens inactivation by UV irradiation - Justad, Kari Elisabeth Takvam (UiT The Arctic University of Norway, 2021)
Open sea cage Atlantic salmon (Salmo salar L.) farming is currently facing major challenges related to sea lice infestations, sea lice treatment, fish mortality, infectious diseases and fish escapees. Semi-closed containment systems may have the potential to resolve these challenges, by separating the rearing unit from the external environment. UV disinfection is suggested as a possible water treatment method, to ensure optimal rearing environment and safe water supply within the system. The necessity and effect of such a treatment on pathogen inactivation needs to be evaluated before being implemented in semi-closed containment systems. There is also a need for more information on specific UV dose requirements to inactivate pathogens infecting farmed salmon during the seawater rearing phase. This study investigates the required reduction equivalent UV doses for complete (99.9%) inactivation of specific Atlantic salmon pathogens, the impact of UV treatment on seawater microbial communities’ equilibrium and the assessment of UV induced DNA damages in a salmon parasite. Bench-scale trials were conducted using two Collimated Beam Apparatus: a low- and medium-pressure UV mercury lamp. The targeted pathogens were Moritella viscosa, the infectious salmon anaemia virus (ISAV) and the ectoparasite Lepeophtheirus salmonis. DNA damages in L. salmonis were assessed using Comet assay analysis. Seawater samples from a salmon farm and a reference station were exposed to UV radiation and the effects on seawater microbial communities’ equilibrium were evaluated. For M. viscosa all UV doses employed in this experiment resulted in an inactivation greater than log 3. The lowest doses were 3 mJ/cm2 using low-pressure UV and 2.3 mJ/cm2 using medium-pressure UV. Contrary to this, none of the UV doses resulted in an inactivation of log 3 or higher in ISAV. The highest inactivation was log 2.59 and was achieved by 22.5 mJ/cm2 with medium-pressure UV. Using low-pressure UV, the highest log inactivation achieved was 2.40 exposed to 2 ...